APPLICATION ECLIPSE OF THE SUN AND THE MOON FOR ELEMENTARY SCHOOL STUDENTS LEARNING USING MACROMEDIA FLASH MX - Mochamad Said AdeSantoso; Ristyawati Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Application Program Eclipses of the Sun and the Moon for Elementary SchoolStudents Learning is a multimedia program that contains some material about theeclipse lessons for children or elementary school students in accordance with theexisting manual current, which is packed in a rather interesting form accompaniedVoice aid. Scientific Writing describes how the Application Program eclipse of theSun and the Moon for Elementary School Students using Macromedia Flash MX andworking under the operating systems Windows 98, Windows ME, XP. It is expectedthat applications can be useful and inspiring primary school students in studying theeclipse or also useful for children just starting to learn.